Assembly and Function of Gonad-Specific Non-Membranous Organelles in Drosophila piRNA Biogenesis - Hirakata, Shigeki (Noncoding RNA, 2019)
PIWI-interacting RNAs (piRNAs) are small non-coding RNAs that repress transposons in animal germlines. This protects the genome from the invasive DNA elements. piRNA pathway failures lead to DNA damage, gonadal development defects, and infertility. Thus, the piRNA pathway is indispensable for the continuation of animal life. piRNA-mediated transposon silencing occurs in both the nucleus and cytoplasm while piRNA biogenesis is a solely cytoplasmic event. piRNA production requires a number of proteins, the majority of which localize to non-membranous organelles that specifically appear in the gonads. Other piRNA factors are localized on outer mitochondrial membranes. In situ RNA hybridization experiments show that piRNA precursors are compartmentalized into other non-membranous organelles. In this review, we summarize recent findings about the function of these organelles in the Drosophila piRNA pathway by focusing on their assembly and function.